Vestibular status: A missing factor in our understanding of brain reorganization in deaf individuals. (May 2021) - Moïn-Darbari, K.; Lafontaine, L.; Maheu, M.; Bacon, B.A.; Champoux, F.
Abstract: The brain of deaf people is definitely not just deaf, and we have to reconsider what we know about the impact of hearing loss on brain development in light of comorbid vestibular impairments.